Sentieri non lineari per la conquista del “sentimento dell’infanzia” nel Novecento: indizi e denunce al MoMa di New York - Mariangela Scarpini (ZoneModa Journal, 2018)
As a matter of fact, little girls and boys have always been but not childhood! Childhood, as a social and cultural construct, exists if it is recognized in the physical and personal data, as in the specific needs, competences and potentials. It is necessary to supply children with environments, times, relationships, educational and daily proposals. For too long this recognition has failed, with the risk of assimilation and homogenisation between the adult world and the children’s, which is still ignored. The twentieth century, also called the century of childhood, sees a progressive attention to the world of childhood, as shown by a growing production of toys, furniture and materials specifically designed for little girls and boys. Even the MoMa of New York, in 2012, staged the exhibition “Century of the Child: Growing by Design, 1900-2000” dedicated to objects designed for infancy in the twentieth century: the path of the conquest of childhood is told through the design and creation of objects, clothes, toys, educational features, tools and materials. The promises made by the twentith century reached their peack in 1989, with the UN Declaration of the Rights of Child, but still most of proclamations often remain fine words. Adults must be responsible towards children and respect their rights in order to let them live a childhood free from the risks of “adultification”, love for spectacle and “showcase-fication”.